A novel glycine transporter-1 (GlyT1) inhibitor, ASP2535 (4-[3-isopropyl-5-(6-phenyl-3-pyridyl)-4H-1,2,4-triazol-4-yl]-2,1,3-benzoxadiazole), improves cognition in animal models of cognitive impairment in schizophrenia and Alzheimer's disease - Harada, Katsuya; Nakato, Kazuhiro; Yarimizu, Junko; Yamazaki, Mayako; Morita, Masahiko; Takahashi, Shinji; Aota, Masaki; Saita, Kyoko; Doihara, Hitoshi; Sato, Yuichiro; Yamaji, Takayuki; Ni, Keni; et al. (European journal of pharmacology, 2012)
Hypofunction of brain N-methyl-d-aspartate (NMDA) receptors has been implicated in psychiatric disorders such as schizophrenia and Alzheimer's disease. Inhibition of glycine transporter-1 (GlyT1) is expected to increase glycine, a co-agonist of the NMDA receptor and, consequently, to facilitate NMDA receptor function. We have identified ASP2535 (4-[3-isopropyl-5-(6-phenyl-3-pyridyl)-4H-1,2,4-triazol-4-yl]-2,1,3-benzoxadiazole) as a novel GlyT1 inhibitor, and here describe our in vitro and in vivo characterization of this compound. ASP2535 potently inhibited rat GlyT1 (IC50=92nM) with 50-fold selectivity over rat glycine transporter-2 (GlyT2). It showed minimal affinity for many other receptors except for μ-opioid receptors (IC50=1.83μM). Oral administration of ASP2535 dose-dependently inhibited ex vivo [3H]-glycine uptake in mouse cortical homogenate, suggesting good brain permeability. This profile was confirmed by pharmacokinetic analysis. We then evaluated the effect of ASP2535 on animal models of cognitive impairment in schizophrenia and Alzheimer's disease. Working memory deficit in MK-801-treated mice and visual learning deficit in neonatally phencyclidine (PCP)-treated mice were both attenuated by ASP2535 (0.3–3mg/kg, p.o. and 0.3–1mg/kg, p.o., respectively). ASP2535 (1–3mg/kg, p.o.) also improved the PCP-induced deficit in prepulse inhibition in rats. Moreover, the working memory deficit in scopolamine-treated mice and the spatial learning deficit in aged rats were both attenuated by ASP2535 (0.1–3mg/kg, p.o. and 0.1mg/kg, p.o., respectively). These studies provide compelling evidence that ASP2535 is a novel and centrally-active GlyT1 inhibitor that can improve cognitive impairment in animal models of schizophrenia and Alzheimer's disease, suggesting that ASP2535 may satisfy currently unmet medical needs for the treatment of these diseases.